2019
DOI: 10.1002/ese3.285
|View full text |Cite
|
Sign up to set email alerts
|

Influence radius of gas extraction borehole in an anisotropic coal seam: Underground in‐situ measurement and modeling

Abstract: Coal seam degasification by in‐seam drilling borehole is one of the popular techniques for coal mine methane (CMM) control. How to address the conflict between borehole numbers and drainage durations always arouses researchers’ interests. Furthermore, since coal has anisotropy structures, how the anisotropy feature of coal associated with bedding and cleat structure affects the influence radius of the drainage borehole has rarely been considered. In order to address the above‐mentioned issues, this work not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The variation of gas pressure with the extraction or mining pressure relief is continuously observed until the gas pressure measurement is completed. When the measured gas pressure drops to a safe range, the effective extraction radius of boreholes can be obtained more accurately by the gas pressure method . In accordance with the Regulations on Prevention and Control of Coal and Gas Outburst, the effective extraction radius can be determined at the maximum gas pressure (0.74 MPa), the maximum gas content (8 m 3 /t), or the gas content decreased by more than 30% .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variation of gas pressure with the extraction or mining pressure relief is continuously observed until the gas pressure measurement is completed. When the measured gas pressure drops to a safe range, the effective extraction radius of boreholes can be obtained more accurately by the gas pressure method . In accordance with the Regulations on Prevention and Control of Coal and Gas Outburst, the effective extraction radius can be determined at the maximum gas pressure (0.74 MPa), the maximum gas content (8 m 3 /t), or the gas content decreased by more than 30% .…”
Section: Introductionmentioning
confidence: 99%
“…At present, the main methods for calculating the effective extraction radius are theoretical calculation, 28,29 field measurement 14,27 and numerical simulation. 30,31 Zhang et al 32 concluded that the extraction radius increased nonlinearly with the borehole radius, while Kong et al 33 found that the relationship between the extraction radius and the borehole radius was linear. This difference in research results is mainly due to the lack of in-depth discussion and unification of the effective extraction radius evaluation criteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Equation (9), the expressions of the obtainable coefficients A, B, C, D, and F can be solved, along with the relation between E and G:…”
Section: Internal Stress Component Solutionmentioning
confidence: 99%
“…In addition, mining-induced fracture aperture is the main channel for aquifer water inrush and gob gas migration. [6][7][8][9] Understanding the failure mechanisms and fracture aperture characteristics plays an important role for establishing a working face early warning system.…”
Section: Introductionmentioning
confidence: 99%